Multi-patch and multi-group model for the transmission of the malaria - Gómez Hernández, Enith Amanda; Ibargüen Mondragón, Eduardo; Salazar Jurado, Edwin Hernando; Prieto Moreno, Kernel Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Malaria is a potentially fatal disease which is caused for parasites transmitted to humans by the bite of female infected mosquitoes of the anopheles gender. Analyzing the effect of mobility and the fact that there are individuals who respond differently to the disease can contribute to the planning of strategies to prevent the spread. In view of the above, it is proposed to study the dynamics of malaria considering that individuals belong to a specific group and are distributed in disjoint plots that are connected in some way. For this, a multipatch and multigroup model is proposed using the Ross-Macdonald model as a basis, in which mobility is incorporated from the Lagrangian approach where all individuals belong to a specific group but spend part of their time in an arbitrary number of patches. The qualitative analysis is performed based on the basic reproductive number and the results showed that the mobility and dividing the population of humans and mosquitoes into groups changing the dynamics of the disease.